Family resilience and demoralization in decompensated cirrhosis: parallel mediation of psychological resilience and social support - Haixia Gao; Gang Mao; Xuelian Gu; Hui Wang; Jianhua Niu; Lei Liu (Frontiers in Psychology)
This study aims to understand the relationship between psychological resilience and social support in family resilience and demoralization syndrome (DS) in decompensated cirrhotic patients and verify whether there is a parallel mediation effect. A cross-sectional design was adopted, and a questionnaire was administered to 260 patients with decompensated cirrhosis in Jinan, Shandong Province, China. The Mandarin Version of the Demoralization Scale (DS-MV) was used to assess DS. Spearman’s correlation was used to analyze the relationship between family resilience, DS, psychological resilience, and social support, and predictors of DS were explored using multiple linear regression. Parallel mediation effect analysis was performed using a bootstrap test. The proportion of patients with severe DS was 18.46% of those with decompensated cirrhosis. Spearman correlation analysis demonstrated that DS was negatively correlated with psychological resilience, family resilience, and social support (r = −0.738, p < 0.01; r = −0.668, p < 0.01; r = −0.405, p < 0.01). Multiple linear regression analysis showed that psychological resilience (β = −0.477, p < 0.001), family resilience (β = −0.364, p < 0.001), and social support (β = −0.108, p = 0.01) could influence DS of decompensated cirrhotic patients. Bootstrap analysis confirmed a significant parallel mediation effect of psychological resilience and social support (95% CI: −0.999 to −0.499), accounting for 51.93% of the total effect. Family resilience had a significant direct effect (95% CI: −0.995 to −0.356), accounting for 48.07% of the total effect. Therefore, attention should be paid to DS in decompensated cirrhotic patients. Family resilience, psychological resilience, and social support can be used to decrease the level of DS.